2005
DOI: 10.1128/jb.187.21.7232-7242.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Physiological Responses to Hydrogen Peroxide of the Facultatively Phototrophic Bacterium Rhodobacter sphaeroides

Abstract: The transcriptome responses to hydrogen peroxide, H 2 O 2 , of the facultatively phototrophic bacterium Rhodobacter sphaeroides grown under semiaerobic conditions were investigated. At 7 min after the addition of 1 mM H 2 O 2 , the expression of approximately 9% of all genes (total, 394) was changed reliably by at least twofold. At 30 min, the number of genes (total, 88) and the magnitude of expression changes were much lower, indicating rapid recovery from stress. Two types of responses were observed: (i) an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 58 publications
7
64
3
Order By: Relevance
“…These results not only underscore the importance of cbb 3 as an oxygen scavenger but also reinforce the relevant role of PpsR as a master regulator of photosystem and its requirement in the protection against photo-oxidative stress when cells are exposed to oxygen and light. This is in agreement with data obtained from R. sphaeroides transcriptome in responses to hydrogen peroxide where down-regulation of the photosynthesis gene is mediated under oxidative stress by the AppA-PpsR regulatory pathway (24).…”
Section: ϫ -Bdsupporting
confidence: 82%
“…These results not only underscore the importance of cbb 3 as an oxygen scavenger but also reinforce the relevant role of PpsR as a master regulator of photosystem and its requirement in the protection against photo-oxidative stress when cells are exposed to oxygen and light. This is in agreement with data obtained from R. sphaeroides transcriptome in responses to hydrogen peroxide where down-regulation of the photosynthesis gene is mediated under oxidative stress by the AppA-PpsR regulatory pathway (24).…”
Section: ϫ -Bdsupporting
confidence: 82%
“…1B). This is in stark contrast to similar studies with other bacteria, in which 140-520 genes were differentially expressed on H 2 O 2 exposure (18)(19)(20)(21)(22)(23) (18,20,23). More surprising was the H 2 O 2 -mediated induction of apiA.…”
Section: Resultscontrasting
confidence: 53%
“…Not surprisingly, A. actinomycetemcomitans displayed enhanced production of the H 2 O 2 -consuming enzyme catalase during coculture. This response has been observed previously in several bacterial species and serves to enhance resistance to H 2 O 2 (18)(19)(20)(21)(22)(23)29). More intriguing was the finding that A. actinomycetemcomitans also induces the outer membrane protein ApiA during coculture.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In contrast to this previous study, we found a significant upregulation of phrA (Fig. 4) and a similar upregulation in rpoE expression (not shown) due to H 2 O 2 stress using real-time RT-PCR and DNA microarray analysis (Zeller et al, 2005).…”
Section: Upregulation Of Phra Expression Depends On Light Intensity Acontrasting
confidence: 55%